Unplanned Immediate Return to Operating Room After Spine Surgery: Significance of Immediate Postoperative Radiographs. Issue 4 (15th February 2019) - Chen, Dennis Q.; Shimer, Adam L.; Li, Xudong; Hassanzadeh, Hamid; Shen, Francis H.; Singla, Anuj
Abstract : Study Design: Retrospective analysis; single center data. Objective: The purpose of this study is to look at the utility and relevance of immediate postoperative radiographs in providing vital information leading to immediate revision after spine surgery. Summary of Background Data: Immediate postoperative radiographs are routinely obtained in the recovery room after spine surgery to verify the level, alignment of the spine, implant position, and the adequacy of the procedure. However, with the ability to utilize intraoperative fluoroscopy imaging for the same purpose, the requirement for immediate postoperative radiographs needs to be validated. The purpose of this study is to look at the utility and relevance of these postoperative radiographs in providing critical information that may warrant immediate intervention. Methods: Retrospective analysis of all spine surgeries (elective and emergent), performed at a single center from 2011 to 2016, was done and cases returning to operating room within 48 hours were identified. Indication of immediate revision was reviewed and utility of immediate postoperative radiographs in guiding immediate revision was analyzed. Results: A total of 1804 elective and urgent spinal surgeries were performed by seven surgeons. Twenty-two patients returned to operating room within 48 hours of their index procedures. Of these 22 cases, only two patients were noted to have positive findings on recovery room radiographs. The findings of suboptimal spinal alignment or failed instrumentation led to the immediate revision in both cases. Both cases involved instrumentation at cervicothoracic region and intraoperative imaging provided only limited visualization. Conclusion: Routine recovery room radiographs played a role in the decision to emergently return to the operating room in 0.10% (2/1804) cases at our institution. The potential benefit of immediate recovery room radiographs after spine surgery should be weighed against the added healthcare cost and patient discomfort associated with obtaining these radiographs routinely. Imaging may be delayed to a more elective time without any significant risk in majority of spine cases. Level of Evidence: 3 Abstract : Post-operative radiographs are commonly obtained in the recovery room after spine surgery. We analyzed the relevance of these radiographs in providing vital information leading to immediate revision after spine surgery. We found limited utility of recovery room imaging with only two of our patients undergoing revision based on postoperative radiographs.